Analysis of the Implementation of Good Corporate Governance Principles in Business Dispute Resolution in Companies in Indonesia - Priyanto, Hengky Budi; Dewanto, Wisnu Aryo; Pattynama, Francis Maryanne (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The principles of Good Corporate Governance (GCG) have become an essential foundation for ensuring business sustainability, stakeholder trust, and competitiveness in modern corporate practices. In Indonesia, the urgency of implementing GCG has increased following corporate scandals that revealed weaknesses in transparency, accountability, and oversight, often resulting in costly business disputes. This study aims to analyze the role of GCG in both preventing and resolving business disputes in Indonesian companies. Using a qualitative method with a systematic literature review, the research integrates findings from scholarly articles, regulatory documents, and case studies. Data were examined through thematic content analysis to identify patterns and relationships between governance practices and dispute outcomes. The results indicate that companies with strong GCG are significantly more effective in dispute prevention and resolution through mechanisms such as arbitration and mediation, thereby minimizing reliance on lengthy litigation. Case studies of PT Bank Century and PT Jiwasraya highlight how governance failures escalated disputes, while examples from PT Telkom illustrate the benefits of transparency and fairness in enabling constructive settlement. The findings suggest that GCG serves a dual role: as a preventive shield reducing the likelihood of disputes and as a dispute-resolution framework ensuring efficiency and fairness when conflicts arise. This study contributes to both academic discourse and practical policy recommendations, emphasizing that GCG is not merely regulatory compliance but a strategic necessity for corporate resilience and sustainable growth in Indonesia.